Water-assisted crystallization of amorphous indium zinc oxide films. (June 2022) - Steigert, Alexander; Kojda, Danny; Ibaceta-Jaña, Josefa; Abou-Ras, Daniel; Gunder, René; Alktash, Nivin; Habicht, Klaus; Wagner, Markus R.; Klenk, Reiner; Raoux, Simone; Szyszka, Bernd; Lauermann, Iver; et al.
Abstract: Transparent conductive materials based on indium oxide remain yet irreplaceable in various optoelectronic applications. Amorphous oxides appear especially attractive for technology as they are isotropic, demonstrate relatively high electron mobility and can be processed at low temperatures. Among them is indium zinc oxide (IZO) with a large zinc content that is crucial for keeping the amorphous state but redundant for the doping. In this work we investigated water-free and water containing IZO films obtained by radio frequency sputtering. The correlation between temperature driven changes of the chemical state, the optical and electrical properties as well as the progression of crystallization was in focus. Such characterization methods as: scanning electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, Raman spectroscopy, temperature dependent Hall-effect measurements and others were applied. Temperature dependent electrical properties of amorphous IZO and IZO:H2 O films were found to evolve similarly. Based on our experience in In2 O3 :H2 O (In2 O3 :H or IOH) we proposed an explanation for the changes observed. Water admixture was found to decrease crystallization temperature of IZO significantly from ∼ 550 °C to ∼ 280 °C. Herewith, the presence and concentration of water and/or hydroxyls was found to determine Zn distribution in the film. In particular, Zn enrichment was detected at the film's surface respective to the high water and/or hydroxyl amount. Raman spectra revealed a two-dimensional crystallization of w -ZnO which precedes regardless water presence an extensive In2 O3 crystallization. An abrupt loss of electron mobility as a result of crystallization was attributed to the formation of ZnO interlayer on grain boundaries.